Status Assessment of Fish Resources Domain Based on The Ecosystem Approach to Management of Frigate Tuna (Auxis thazard) Fishery in Lombok Strait Waters Landed in East Seraya Village, Bali: Penilaian Status Domain Sumber Daya Ikan Berdasarkan Pendekatan Ekosistem untuk Pengelolaan Perikanan Tongkol Krai (Auxis thazard) di Perairan Selat Lombok yang Didaratkan di Desa Seraya Timur, Bali - I Putu Yoga Pramana Putra; I Wayan Arthana; Made Ayu Pratiwi (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
East Seraya Village is one of the villages as the centers of Frigate Tuna fishery in Karangasem Regency, Bali. Frigate tuna (Auxis thazard) is a main commodity of the fisherman catch. This study aimed to assess the status of fish resources domains based on an ecosystem approach to the management of Frigate Tuna (Auxis thazard) fishery in Lombok Strait Waters landed in East Seraya Village. This research was conducted from November 2019 to January 2020. Data collecting in this research was carried out by field observation, survey, and interviews. Data analysis was performed on each indicator using a multi-criteria analysis with composite index assessment and flag model visualizations. The observed indicators are CPUE trend, fish size trend, the juvenile fish proportion, the catch composition, range collapse of fish resources, and ETP species (Endangered, Threatened, and Protected Species). The assessment of status fish resources domain based on an ecosystem approach to the management of Frigate Tuna (Auxis thazard) fishery in Lombok Strait Waters landed in East Seraya Village was good category with a composite value of 61,67. The fish resources domain indicator showed the CPUE trend has been annually decreased of 7,80%, fish size trend are relatively fixed, the juvenile fish proportion was 100%, the catch composition is dominated bycatch target fish both from gillnet and trolling fishing gear with each percentage of 98% and 90.7%, range collapse of fish resources for fishing is increasingly difficult, and ETP species (Endangered, Threatened, and Protected Species) caught was in a very small amount.